A prototype for cartographic human body analysis - Carvalho, Elizabeth Simão (2008)
Medicine is a vast area of scientific inquiry that uses many computer imageprocessing applications such as x-rays, ultrasound, computed tomography (CT), and magnetic resonance imaging (MRI). Besides image processing, computer graphics have addressed many other medical science issues, including human- body modeling, diagnostic decision-support, and training systems. Graphics provide a powerful means of delivering information, but if an advanced graphics application fails to process its input data properly, the graphics become worthless. A good visualization pipeline depends heavily on the application model that converts the data to graphics. Medical knowledge has distinct characteristics that any model in this domain must consider. It doesn’t typically deal with the kinds of data present in business applications. Instead, its data belongs to something that’s alive, with signifi cant morphological and intrinsically anatomical aspects. Any medical software application should merge visualization’s strong potentialities with a model well tailored to these data characteristics and medical-task processes.1 We propose a cartographic-oriented model to visualize and analyze medical data relative to the human body. A prototype implementation has proved the viability and long-term promise of this approach in two case studies.